Belatacept and carfilzomib-based treatment for antibody-mediated rejection in a sensitized nonhuman primate kidney transplantation model - Schmitz, Robin; Manook, Miriam; Fitch, Zachary; Anwar, Imran; DeLaura, Isabel; Olaso, Danae; Choi, Ashley; Yoon, Janghoon; Bae, Yeeun; Song, Mingqing; Farris, Alton B.; Kwun, Jean; et al. (Frontiers in Transplantation, 2023)
One-third of HLA-incompatible kidney transplant recipients experience antibody mediated rejection (AMR) with limited treatment options. This study describes a novel treatment strategy for AMR consisting of proteasome inhibition and costimulation blockade with or without complement inhibition in a nonhuman primate model of kidney transplantation. All rhesus macaques in the present study were sensitized to maximally MHC-mismatched donors by two sequential skin transplants prior to kidney transplant from the same donor. All primates received induction therapy with rhesus-specific ATG (rhATG) and were maintained on various immunosuppressive regimens. Primates were monitored postoperatively for signs of acute AMR, which was defined as worsening kidney function resistant to high dose steroid rescue therapy, and a rise in serum donor-specific antibody (DSA) levels. Kidney biopsies were performed to confirm AMR using Banff criteria. AMR treatment consisted of carfilzomib and belatacept for a maximum of four weeks with or without complement inhibitor. Treatment with carfilzomib and belatacept was well tolerated and no treatment-specific side effects were observed. After initiation of treatment, we observed a reduction of class I and class II DSA in all primates. Most importantly, primates had improved kidney function evident by reduced serum creatinine and BUN as well as increased urine output. A four-week treatment was able to extend graft survival by up to two months. In summary, combined carfilzomib and belatacept effectively treated AMR in our highly sensitized nonhuman primate model, resulting in normalization of renal function and prolonged allograft survival. This regimen may translate into clinical practice to improve outcomes of patients experiencing AMR.